People's Republic of China : 2019 Article IV Consultation-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for China. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation with People's Republic of China highlights that after the slowdown in 2018, reflecting financial regulatory strengthening and softening external demand, growth stabilized in early 2019. Financial deleveraging and reduced interconnectedness between banks and non-banks have helped contain the build-up of financial risks, but vulnerabilities remain elevated and progress on rebalancing is mixed. While a moderate slowdown is expected in 2019, uncertainty around trade tensions remains high and risks are tilted to the downside. Successfully shifting from high-speed to high-quality growth in a highly uncertain environment requires stabilizing the economy amid rising trade tensions while continuing with deleveraging and strengthening rebalancing. It is important to improve external policies and frameworks by working constructively with trading partners to better address shortcomings and enable a trading system that can more readily adapt to economic changes in the international environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet